Network toxicology and molecular docking analyses on strychnine indicate CHRM1 is a potential neurotoxic target - Jialin Dai; Jiangjin Liu; Maoxin Zhang; Yanni Yu; Jie Wang (BMC Complementary Medicine and Therapies, 2022)
Abstract Background Improper use of strychnine can cause death. The aim of this study was to identify and evaluate toxic mechanisms of action associated with active compounds in strychnine using a network toxicology approach, and explore potential pathogenic targets. Methods In the present study, strychnine target and central nervous system-related gene set were established using the Traditional Chinese Medicine Systems Pharmacology (TCMSP) database and four disease gene databases (Genecards, OMIM, PharmGkb, TTD). An “ingredient-target” interactive active network map was constructed using Cytoscape software (version 3.8.0). Functional enrichment analysis was performed based on the hub genes. A protein-protein interaction network was constructed using STRING database. The pharmacokinetics (ADMET) properties of strychnine were evaluated using SwissADME tool. Molecular docking was performed using Autodock Vina to explore the interactions between the active compounds and the target protein. Results Five strychnine toxicity-related components and a gene set of 40 genes were obtained. GO and KEGG analyses showed that Strychnine acts on the central nervous system through G protein-coupled receptor signaling pathway. Analysis of “ADMET” related parameters showed a high gastrointestinal tract absorption of (S)-stylopine and isobrucine and the compounds could cross the blood brain barrier. CHRM1 was selected as a key gene in strychnine toxicity. Molecular docking results showed that the co-crystalized ligands did not form hydrogen bond with CHRM1. (S)-stylopine had the highest binding affinity (binding energy = − 8.5 kcal/mol) compared with the other two compounds. Conclusion Network toxicology and molecular docking reveal the toxicity mechanisms of strychnine active compounds. The findings showed that CHRM1 is a potential neurotoxic target. (S)-stylopine showed stronger neurotoxic effect compared with the other ligands.